HUBUNGAN ANTARA AKTIVITAS OLAHRAGA DENGAN KEMAMPUAN MEMECAHKAN MASALAH - CANDRA HADI LUKMANA, R. (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract Problem solving is a proces mental and intelectual to find and solve  the problem with data and acuration information, so it can be decided perfectly. Physical education through sport  activities aimed to build in cognitive, affective, and psychomotor aspects. Sport activities are taught that one makes decicions. Therefore, it is expected, through sport activities, to create opprtunities for students, to take the values of sport to enhance their problem solving skill. The purpose of this research was to figure out how deep the relationship between sport activity and problem solving skill. It was non-experimental reserch with design correlation. The population was all sevent grade students of SMPN 3 Nganjuk which consist of 295 students. While the sampling technique which used was random sampling and there were 63 samples. Its instrument was test and questionnaire. Product Moment Correlation was used to analyze the data. Analysis result showed the lowest score of the sport activity questionnaire was 4, while the highest was 13. The mean was 7.76 with 2.17 of deviation standart. The lowest score of problem solving skill tests was 43 and the highest was 73. The mean was 61.13 with 8.03 of deviation standart. Product Moment correlation result was at 0.05 significance level with n=63. It could be determined that r count was greater than r table (r count 0,264 > r table 0,241) with 6,97%determination coefecient. It could be drawn thatthere was significant relationship between sport activity and problem solving skill of SMPN 3 Nganjuk students, r count = 0,264. Key words: Sport Activity, Problem Solving